The Role of Social Parameters in the Choice of Address Forms used in Kinship domain in Punjab, Pakistan - Ana Ramsha; Samrah Hidayat (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2019)
This study examines the role of social parameters in the choice of address forms used in kinship domain in Punjab, Pakistan. The study targeted 140 respondents in order to test the impact of social factors along with the regional differences in the choices of address forms in kinship domain. Statistical analyses are done by applying t-test for gender in relation to choices of address forms and ANOVA for age, income, education and social class. The study finds out that there is a strong connection of different social parameters not only with language use and practice but also in choices and use of address forms especially in kinship relationships. Moreover, it is highlighted that gender does not influence in the choices of address forms, even the participants belonging to young and middle categories show no significant difference with regard to the choices of address form despite the fact that all the factors and parameters exert influence on the choices of address forms. Hence address forms as being one of the major traits of language and society is affected by all the social factors around and regional differences are also most important as they give identity and ethnicity to the society.